Synthesis of NiO/Zeolite Catalyst and Its Performance in Renewable Biomass Gasification Electric Generator - Niyartama, Thaqibul Fikri; Widiakongko, Priyagung Dhemi (Kaunia: Integration and Interconnection Islam and Science Journal, 2025)
Research on NiO/Zeolite catalytic biomass gasification to produce electricity has been completed. This study aims to study the effect of the NiO/Zeolite catalyst on the voltage and current generated in the gasification process. This research was carried out by making NiO/Zeolite catalysts using the wet impregnation method, followed by contructing a gasification device plus installing a batch of catalysts in the reactor, and then testing the electrical parameters produced by the gasification equipment. The results obtained are NiO/Zeolite catalysts which have been successfully synthesized using FTIR spectral indicators and XRD diffractograms with the appearance of NiO and Ni peaks at angles of 2θ 28o and 63o. The resulting catalyst was also reported to have succeeded in increasing voltage stability compared to the gasification process without a catalyst with a maximum value of 250 V and an average value of 225 V. The NiO/Zeolite catalyst also succeeded in increasing the current value and stabilizing the current value compared to the non-reaction gasification process with a maximum of 50 A and an average of 44 A.